Statistical Yearbook for Asia and the Pacific 2013 - Nations Unies (United Nations, 2013)
This publication presents data for the 58 ESCAP member countries, as well as world, regional, sub-regional and economic aggregates for comparison. It offers current trends and emerging topics in the Asia-Pacific region, grouped around the themes of people, the environment, the economy and connectivity. It provides the international and regional community with key indicators, objective analyses of the current trends and emerging issues, along with data and charts. In order to maximize the comparability, the data is sourced exclusively from international agencies that adhere to the official global statistical standards.